Does Polypharmacy in Nursing Homes Affect Long‐Term Mortality?. Issue 7 (15th June 2016) - Schlesinger, Agata; Weiss, Avraham; Nenaydenko, Olga; Adunsky, Abraham; Beloosesky, Yichayaou
Abstract : Objectives: To investigate the association between polypharmacy and mortality in nursing home (NH) residents. Design: Prospective observational cohort study. Settings: Six NHs in central Israel. Participants: Mobile with dementia and fully dependent residents (N = 764; n = 558 (73%) fully dependent, n = 206 (27%) mobile residents with dementia requiring institutional care; mean age 82.2 ± 5.9). Measurements: Two‐year mortality and its association with number of drugs that individual residents were taking at baseline, controlled for multiple confounders. Results: At baseline, 268 residents were taking five or fewer drugs per day, 202 were taking six or seven, and 294 were taking eight or more. In the multivariate analysis, the likelihood of dying within 2 years in the group taking six or seven drugs per day (odds ratio (OR = 0.95, 95% CI = 0.63–1.43) and in those taking eight or more (OR = 1.20, 95% CI = 0.78–1.84) was similar to that of those taking five or fewer. Variables at baseline independently associated with greater mortality were male sex (OR = 1.75, 95% CI = 1.24–2.46), older age (OR = 1.07, 95% CI = 1.04–1.10), higher Charlson Comorbidity Index (OR = 1.17, 95% CI = 1.04–1.30), and taking anticoagulant (OR = 1.78, 95% CI = 1.01–3.13) or antihyperglycemic medication (OR = 1.69, 95% CI = 1.12–2.53). Variables at baseline independently associated with lower mortality were higher body mass index (OR = 0.99, 95% CI = 0.93–0.99) and taking lipid‐lowering medication (OR = 0.54, 95% CI = 0.36–0.80) and selective serotonin reuptake inhibitors or serotonin–norepinephrine reuptake inhibitors (OR = 0.52, 95% CI = 0.37–0.75). Conclusion: Polypharmacy, defined quantitatively according to number of drugs, was not associated with mortality in these NH residents.